1981
DOI: 10.1111/j.1476-5381.1981.tb16803.x
|View full text |Cite
|
Sign up to set email alerts
|

The EFFECT OF ANAESTHETICS ON THE UPTAKE AND RELEASE OF Γ‐AMINOBUTYRATE AND D‐ASPARTATE IN RAT BRAIN SLICES

Abstract: The effect of various concentrations of thiopentone, pentobarbitone, methohexitone, hydroxydione, alphaxalone/alphadolone, ketamine, α‐chloralose and urethane on the transport of radiolabelled γ‐aminobutyric acid (GABA) and D‐aspartate was investigated. Uptake of the amino acids was weakly inhibited, if at all, by the anaesthetics and it is unlikely that such effects contribute significantly to their physiological function. The spontaneous efflux of GABA and D‐aspartate was not detectably altered by any of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
2

Year Published

1982
1982
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 33 publications
5
35
2
Order By: Relevance
“…The increase in net glutamate out¯ow at reduced release and suppressed re-uptake suggests that under the control condition when re-uptake mechanism works normally, the majority of released glutamate is taken up before di using into the ACSF. Thus, although some direct measurements of neurotransmitter re-uptake have concluded that uptake of glutamate or GABA may not play a signi®cant role in the action of thiopentone, pentobarbitone, methohexitone, altesin, ketamine, halothane, or urethane (Gri ths & Norman, 1993;Kendall & Minchin, 1982;Minchin, 1981), it seems too early at present time to rule out the possible involvement of neurotransmitter re-uptake in the intricate balance of neuronal events that lead to general anaesthesia (Miyazaki et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The increase in net glutamate out¯ow at reduced release and suppressed re-uptake suggests that under the control condition when re-uptake mechanism works normally, the majority of released glutamate is taken up before di using into the ACSF. Thus, although some direct measurements of neurotransmitter re-uptake have concluded that uptake of glutamate or GABA may not play a signi®cant role in the action of thiopentone, pentobarbitone, methohexitone, altesin, ketamine, halothane, or urethane (Gri ths & Norman, 1993;Kendall & Minchin, 1982;Minchin, 1981), it seems too early at present time to rule out the possible involvement of neurotransmitter re-uptake in the intricate balance of neuronal events that lead to general anaesthesia (Miyazaki et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies, e.g. Minchin (1981), suggest that this potentiation is not the re- sult-of altered GABA uptake mechanisms. We are unaware of any other studies using ketamine that are directly comparable with ours.…”
Section: Anaesthetics Differ In Theirpostsynaptic Effectsmentioning
confidence: 97%
“…Anaesthesia was assessed according to the criteria of McFarland (1981). Assumptions (Minchin, 1981) (1959). The anaesthetics were dissolved in river water to the same concentrations as were employed in the iontophoresis experiments and each drug was tested on a minimum of 6 ammocoetes.…”
Section: Appendixmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrophysiological analysis has demonstrated that concentrations of barbiturates within the anaesthetic range do not interfere significantly with the propagation of the nerve impulse, but they inhibit the release of putative neurotransmitters such as glutamate from synaptosomes and slices of brain tissue (see Collins, 1981;Minchin, 1981;Kendall & Minchin, 1982). Moreover, Blaustein & Ector (1974) have shown that concentrations of barbiturates within the anaesthetic range depress the K'-stimulated Ca2+ influx into synaptosomes, but these authors did not correlate this decrease in Ca2+ flux with changes in transmitter release.…”
Section: Implicationsfor Anaesthetic Action In the Cnsmentioning
confidence: 99%